Phonon Kinetics of Fructose at the Melting Transition - A. Davie; F. Vandrevala; S. Dampf; Y. Deng; D. K. George; E. D. Sylvester; T. Korter; E. Einarsson; J. B. Benedict; A. G. Markelz (J. Phys. Chem. C, 2021)
Terahertz time domain spectroscopy (THz TDS) is used to measure the melting kinetics of fructose molecular crystals. Combining single-crystal anisotropy measurements with density functional calculations, we assign the phonon frequencies and interrogate how specific phonons behave with melting. While nearly all the low-frequency phonons continuously red-shift with heating and melting, the lowest-energy phonon polarized along the c-axis blue-shifts at the melting temperature, suggesting an initial structural change immediately before melting. We find that the kinetics follow a 3D growth model with large activation energies, consistent with previous differential scanning calorimetry (DSC) measurements. The large activation energies indicate that multiple H-bonds must break collectively for the transition. The results suggest the generality of the kinetics for molecular crystals and that THz TDS with picosecond resolution could be used to measure ultrafast kinetics.

Blue Shift of a Molecular Crystal Phonon at the Solid to Liquid Phase Transition - Davie, Alex; Vandrevala, Farah; Deng, Yanting; George, D.; Sylvester, Eric D.; Korter, T.; Einarsson, E.; Benedict, Jason B.; Markelz, Andrea (Bulletin of the American Physical Society, 2019)

Tunable Compact Narrow Band THz Sources for Frequency Domain THz Anisotropic Spectroscopy - George, D. K.; LaFave, T. J.; Markelz, A. G.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P. (Conference on Next-Generation Spectroscopic Technologies XII, 2019)
We demonstrate frequency domain THz anisotropy signature detection for protein crystal models using newly developed compact tunable narrow band THz sources based on Orientation Patterned Gallium Phosphide for turn-key spectroscopic systems.
Keywords: anisotropy; biomolecules; femtosecond; optical rectification; orientation patterned gallium phosphide; Terahertz; THz generation

Increase in Dynamical Collectivity and Directionality of Orange Carotenoid Protein in the Photo-Protective State - Deng, Y. T.; Luck, C. H.; Romo, T. D.; Grossfield, A. M.; Bandara, S.; Ren, Z.; Yang, X. J.; Markelz, A. G. (Biophysical Journal, 2018)
Keywords: Biophysics

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Global Picosecond Structural Dynamics of Orange Carotenoid Protein in Photo/Chemical Activated Signaling States - Deng, Y.; Xu, M.; Liu, H.; Blankenship, R.; Markelz, A. (APS 2017 S4.002, 2017)

Orange Carotenoid Protein Picosecond Dynamics Changes with Photo and Chemical Activation - Deng, Y. T.; Xu, M. Y.; Liu, H. J.; Blankenship, R. E.; Markelz, A. G. (Biophysical Journal, 2017)
Keywords: Biophysics

Temperature dependence of phonons in photosynthesis proteins - Xu, M.; Myles, D.; Blankenship, R.; Markelz, A. (APS 2017 S4.003, 2017)

Modulated orientation-sensitive terahertz spectroscopy - Singh, R.; George, D. K.; Bae, C. J.; Niessen, K. A.; Markelz, A. G. (Photonics Research, 2016)
Intramolecular vibrations of large macromolecules reside in the terahertz range. In particular, protein vibrations are closely spaced in frequency, resulting in a nearly continuous vibrational density of states. This density of vibrations interferes with the identification of specific absorption lines and their subsequent association with specific functional motions. This challenge is compounded with the absorption being dominated by the solvent and local relaxational motions. A strategy for removing the isotropic relaxational loss and isolating specific vibrations is to use aligned samples and polarization-sensitive measurements. Here, we demonstrate a technique to rapidly attain the anisotropic resonant absorbance using terahertz time domain spectroscopy and a spinning sample. The technique, modulated orientation-sensitive terahertz spectroscopy (MOSTS), has a nonzero signal only for anisotropic samples, as demonstrated by a comparison between a silicon wafer and a wire grid polarizer. For sucrose and oxalic acid molecular crystals, the MOSTS response is in agreement with modeled results for the intermolecular vibrations. Further, we demonstrate that, even in the presence of a large relaxational background, MOSTS isolates underlying vibrational resonances. (C) 2016 Chinese Laser Press
Keywords: absorption-spectroscopy; dynamics; enzyme catalysis; low-frequency modes; lysozyme; neutron-scattering; Optics; perspective; polarization modulation; proteins; water

Measuring phonons in protein crystals - Acbas, G.; Niessen, K. A.; George, D. K.; Snell, E.; Markelz, A. G. (Ultrafast Phenomena and Nanophotonics Xvii, 2013)
Using Terahertz near field microscopy we find orientation dependent narrow band absorption features for lysozyme crystals. Here we discuss identification of protein collective modes associated with the observed features. Using normal mode calculations we find good agreement with several of the measured features, suggesting that the modes arise from internal molecular motions and not crystal phonons. Such internal modes have been associated with protein function.
Keywords: correlated motions; dynamics; mode; molecular crystals; molecular vibrations; normal modes; phonons; protein dynamics; spectroscopy; Terahertz

Photoactive yellow protein terahertz response: hydration, heating and intermediate states - George, Deepu K; Knab, Joseph R; He, Yunfen; Kumauchi, Masato; Birge, Robert R; Hoff, Wouter D; Markelz, Andrea G (IEEE Transactions on Terahertz Science and Technology, 2013)

Improved mode assignment for molecular crystals through anisotropic terahertz spectroscopy - Singh, Rohit; George, Deepu Koshy; Benedict, Jason B; Korter, Timothy M; Markelz, Andrea G (The Journal of Physical Chemistry A, 2012)

Terahertz Response and Colossal Kerr Rotation from the Surface States of the Topological Insulator Bi2Se3 - Aguilar, R. V.; Stier, A. V.; Liu, W.; Bilbro, L. S.; George, D. K.; Bansal, N.; Wu, L.; Cerne, J.; Markelz, A. G.; Oh, S.; Armitage, N. P. (Physical Review Letters, 2012)
We report the THz response of thin films of the topological insulator Bi2Se3. At low frequencies, transport is essentially thickness independent showing the dominant contribution of the surface electrons. Despite their extended exposure to ambient conditions, these surfaces exhibit robust properties including narrow, almost thickness-independent Drude peaks, and an unprecedentedly large polarization rotation of linearly polarized light reflected in an applied magnetic field. This Kerr rotation can be as large as 65 degrees and can be explained by a cyclotron resonance effect of the surface states.
Keywords: bi2te3; Physics

Terahertz response of quantum point contacts - Song, J. W.; Kabir, N. A.; Kawano, Y.; Ishibashi, K.; Aizin, G. R.; Mourokh, L.; Reno, J. L.; Markelz, A. G.; Bird, J. P. (Applied Physics LettersApplied Physics LettersApplied Physics Letters, 2008)
We measure a clear terahertz response in the low-temperature conductance of a quantum point contact at 1.4 and 2.5 THz. We show that this photoresponse does not arise from a heating effect, but that it is instead excellently described by a classical model of terahertz-induced gate-voltage rectification. This effect is distinct from the rectification mechanisms that have been studied previously, being determined by the phase-dependent interference of the source drain and gate voltage modulations induced by the terahertz field. (C) 2008 American Institute of Physics.
Keywords: detector; devices; field-effect transistors; Physics; plasma-waves; radiation; resonant detection; subterahertz; transport

Terahertz spectroscopy of bacteriorhodopsin and rhodopsin: Similarities and differences - Balu, R.; Zhang, H.; Zukowski, E.; Chen, J. Y.; Markelz, A. G.; Gregurick, S. K. (Biophysical Journal, 2008)
We studied the low-frequency terahertz spectroscopy of two photoactive protein systems, rhodopsin and bacteriorhodopsin, as a means to characterize collective low-frequency motions in helical transmembrane proteins. From this work, we found that the nature of the vibrational motions activated by terahertz radiation is surprisingly similar between these two structurally similar proteins. Specifically, at the lowest frequencies probed, the cytoplasmic loop regions of the proteins are highly active; and at the higher terahertz frequencies studied, the extracellular loop regions of the protein systems become vibrationally activated. In the case of bacteriorhodopsin, the calculated terahertz spectra are compared with the experimental terahertz signature. This work illustrates the importance of terahertz spectroscopy to identify vibrational degrees of freedom which correlate to known conformational changes in these proteins.
Keywords: Biophysics; bovine rhodopsin; conformational-changes; elastic; frequency normal-modes; light activation; molecular-dynamics simulation; neutron-scattering; protein-coupled receptors; transmembrane helices; vibrational-modes; wild-type

Terahertz transmission characteristics of high-mobility GaAs and InAs two-dimensional-electron-gas systems - Kabir, N. A.; Yoon, Y.; Knab, J. R.; Chen, J. Y.; Markelz, A. G.; Reno, J. L.; Sadofyev, Y.; Johnson, S.; Zhang, Y. H.; Bird, J. P. (Applied Physics Letters, 2006)
Frequency-dependent complex conductivity of high-mobility GaAs and InAs two-dimensional-electron-gas (2DEG) systems is studied by terahertz time domain spectroscopy. Determining the momentum relaxation time from a Drude model, the authors find a lower value than that from dc measurements, particularly at high frequencies/low temperatures. These deviations are consistent with the ratio tau(t)/tau(q,) where tau(q) is the full scattering time. This suggests that small-angle scattering leads to weaker heating of 2DEGs at low temperatures than expected from dc mobilit9y. (c) 2006 American Institute of Physics.
Keywords: field-effect transistors; photoconductivity; Physics; plasma-waves; radiation; resonant detection; subterahertz

Terahertz measurements of the Photoactive Protein Bacteriorhodopsin mutant D96N: M and P states - Chen, C.-Y.; Knab, J. R.; Cerne, J.; Hillebrecht, J. R.; Birge, R. R.; Markelz, A. G. (Mater. Res. Soc. Symp., 2004)
We use terahertz (THz) spectroscopy as a biomaterials characterization tool. Previously we have shown a strong contrast between the THz dielectric response for wild type (WT) and D96N mutant of bacteriorhodopsin. In those studies we observed a large increase in the THz absorbance of WT with excitation to thermally captured photo-intermediates whereas no such increase in absorbance was observed for the mutant D96N. These results suggest that the THz response is sensitive to structural changes and relative flexibility of biomolecules. However the photo-intermediate populations of the WT and D96N samples were not equivalent in those measurements. While the WT samples had relaxed (bR), M and P state intermediates present, the D96N samples had only bR and M states. Here we present terahertz absorbance measurements of D96N as a function of M and P state populations at room temperature. The THz response is constant for intermediate states populations up to 23% M state and up to 30% P state. These results verify that there is a fundamental difference in the conformational dynamics as measured by THz dielectric response for a single residue mutation.

Protein flexibility and conformational state: A comparison of collective vibrational modes of wild-type and D96N bacteriorhodopsin - Whitmire, S. E.; Wolpert, D.; Markelz, A. G.; Hillebrecht, J. R.; Galan, J.; Birge, R. R. (Biophysical Journal, 2003)
Far infrared ( FIR) spectral measurements of wild-type (WT) and D96N mutant bacteriorhodopsin thin films have been carried out using terahertz time domain spectroscopy as a function of hydration, temperature, and conformational state. The results are compared to calculated spectra generated via normal mode analyses using CHARMM. We find that the FIR absorbance is slowly increasing with frequency and without strong narrow features over the range of 2-60 cm(-1) and up to a resolution of 0.17 cm(-1). The broad absorption shifts in frequency with decreasing temperature as expected with a strongly anharmonic potential and in agreement with neutron inelastic scattering results. Decreasing hydration shifts the absorption to higher frequencies, possibly resulting from decreased coupling mediated by the interior water molecules. Ground-state FIR absorbances have nearly identical frequency dependence, with the mutant having less optical density than the WT. In the M state, the FIR absorbance of the WT increases whereas there is no change for D96N. These results represent the first measurement of FIR absorbance change as a function of conformational state.
Keywords: angstrom resolution; Biophysics; dna; films; frequency; harmonic-analysis; inelastic neutron-scattering; large systems; mixed basis; normal-modes; purple membranes; structural-changes; transform infrared-spectroscopy

Terahertz Biosensors based on Xerogel Substrates - Chen, J.-Y.; Cox, W.; Bright, F. V.; Cerne, J.; Markelz, A. G. (Proceedings of the International Symposium on Spectral Sensing Research, 2003)

Ultrafast THz spectroscopy of photoactive biomolecules - Chen, J.-Y.; Whitmire, S. E.; Markelz, A. G.; Hillebrecht, J. R.; Birge, R. R. (Ultrafast Phenomena in Semiconductors VII, 2003)

THz time domain spectroscopy of biomolecular conformational modes - Markelz, Andrea; Whitmire, Scott; Hillebrecht, Jay; Birge, Robert (Physics in Medicine & Biology, 2002)

Terahertz Time domain spectroscopy of the M intermediate state of Bacteriorhodopsin - Whitmire, S.; Markelz, A. G.; Hillebrecht, J. R.; Birge, R. R. (Proceedings of the 26th International Conference on Infrared and Millimeter Waves, 2001)

Interband impact ionization by terahertz illumination of InAs heterostructures - Markelz, A. G.; Asmar, N. G.; Brar, B.; Gwinn, E. G. (Applied Physics Letters, 1996)
Experimental studies of InAs heterostructures illuminated by far-infrared (FIR) radiation reveal an abrupt increase in the charge density for FIR intensities above a threshold value that rises with increasing frequency. We attribute this charge density rise to interband impact ionization in a regime in which omega tau(m) similar to 1, where tau(m) is the momentum relaxation time, and f=omega/2 pi is the FIR frequency. The dependence of the density rise on the FIR field strength supports this interpretation, and gives threshold fields of 3.7-8.9 kV/cm for the frequency range 0.3-0.66 THz. (C) 1996 American Institute of Physics.
Keywords: energy; far-infrared excitation; inas/alsb quantum-wells; inplane; modulation; Physics

Third Harmonic Generation in a Gaas/Algaas Superlattice in the Bloch Oscillator Regime - Wanke, M. C.; Markelz, A. G.; Unterrainer, K.; Allen, S. J.; Bhatt, R. (Hot Carriers in Semiconductors, 1996)

QUENCHING OF EXCITONIC QUANTUM-WELL PHOTOLUMINESCENCE BY INTENSE FAR-INFRARED RADIATION - FREE-CARRIER HEATING - Cerne, J.; Markelz, A. G.; Sherwin, M. S.; Allen, S. J.; Sundaram, M.; Gossard, A. C.; Vanson, P. C.; Bimberg, D. (Physical Review B, 1995)

Third harmonic generation in a GaAs/AlGaAs Superlattice in the Bloch Oscillator Regime - Wanke, M. C.; Markelz, A.G.; Unterrainer, K.; Allen, S. J.; Bhatt, R. (Proceedings of the International Conference on Hot Carriers in Seminconductors, 1995)

Frequency Dependence of the Third Order Susceptibility of InAs Quantum Wells at Terahertz Frequencies - Markelz, A.G.; Cerne, J.; Gwinn, E. G.; Brar, B.; Kroemer, H. (Proceedings of the International Conference on the Physics of Semiconductors, 1994)

Far-infrared nonlinear response of electrons in semiconductor nanostructures - Sherwin, M. S.; Asmar, N. G.; Bewley, W. W.; Craig, K.; Felix, C. L.; Galdrikian, B.; Gwinn, E. G.; Markelz, A.G.; Gossard, A. C.; Hopkins, P. F.; Sundaram, M.; Birnir, B. (SPIE Proceedings, 1993)

Conversion of 124 and 123 + cupric oxide: microstructure and phase diagram - Morris, D. E.; Nickel, J. H.; Markelz, A.G.; Gronksy, R.; Fendorf, M.; Burmester, C. P. (Materials Research Society Symposium Proceedings, 1990)